2017
DOI: 10.1186/s13012-016-0537-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-strategic intervention to enhance implementation of healthy canteen policy: a randomised controlled trial

Abstract: BackgroundInternationally, governments have implemented school-based nutrition policies to restrict the availability of unhealthy foods from sale. The aim of the trial was to assess the effectiveness of a multi-strategic intervention to increase implementation of a state-wide healthy canteen policy. The impact of the intervention on the energy, total fat, and sodium of children’s canteen purchases and on schools’ canteen revenue was also assessed.MethodsAustralian primary schools with a canteen were randomised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
162
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 89 publications
(172 citation statements)
references
References 34 publications
8
162
0
2
Order By: Relevance
“…Recruitment was conducted among all primary schools (enrolling children aged 5‐12 years) in the study region identified via health service record as having an operational canteen (n = 338). Schools were ineligible if they catered for students with special needs, juvenile justice or hospitalised children or if they were involved in trials conducted by the research team …”
Section: Methodsmentioning
confidence: 99%
“…Recruitment was conducted among all primary schools (enrolling children aged 5‐12 years) in the study region identified via health service record as having an operational canteen (n = 338). Schools were ineligible if they catered for students with special needs, juvenile justice or hospitalised children or if they were involved in trials conducted by the research team …”
Section: Methodsmentioning
confidence: 99%
“…To bridge this evidence‐practice gap, a randomised controlled trial (RCT) was conducted in one region of New South Wales (NSW), Australia. The trial aimed to increase the implementation of the mandatory state canteen policy Fresh Tastes @ School NSW Healthy School Canteen Strategy (hereafter referred to as Fresh Tastes @ School).…”
Section: Introductionmentioning
confidence: 99%
“…The trial aimed to increase the implementation of the mandatory state canteen policy Fresh Tastes @ School NSW Healthy School Canteen Strategy (hereafter referred to as Fresh Tastes @ School). At intervention completion (12 months post baseline), schools receiving implementation support were significantly more likely to adhere to the policy . Although the findings are encouraging, the benefits of implementation support strategies are maximised if their effects are maintained in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…>80% of schools and childcare services), led to significant improvements in the adoption of policies and practices across community settings, improved student dietary intake and physical activity, and reduced population prevalence of child obesity by 1% per year against an otherwise increasing prevalence in the rest of the state. 10 These successful interventions and implementation support strategies have subsequently been adopted as routine service delivery practice by HNELHD in supporting 420 primary schools and 350 childcare services to promote healthy eating and physical activity. These implementation trials were among the first of their kind and contributed an early and substantive body of evidence to an emerging field of implementation science in community settings.…”
mentioning
confidence: 99%
“…3,4 Rigorous controlled evaluations of the service delivery models provided evidence for 'how' community settings could be re-oriented to more effectively deliver obesity prevention services at scale. 10 At a NSW level, GfK provided evidence for achieving state-wide impact at a time of significant national and state investment through the National Partnership Agreement Editorial on Preventive Health. 5,6 Evidence generated from GfK had a profound impact on population health services locally and in NSW.…”
mentioning
confidence: 99%